2018
DOI: 10.1093/ons/opy219
|View full text |Cite
|
Sign up to set email alerts
|

Abdominal Fat Graft for Sellar Reconstruction: Retrospective Outcomes Review and Technical Note

Abstract: Minimizing postoperative CSF leaks following endonasal anterior skull base surgery is important to decrease morbidity and to avoid a prolonged hospital stay. We present an evolved technique of abdominal fat grafting that is effective and safe and includes minimal morbidity and expense.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 56 publications
1
36
0
Order By: Relevance
“…Although, this is a common site for many neurosurgeons and no incision siterelated complications occurred in the present study, some authors suggest a periumbilical incision for better cosmetic results (►Table 2). 13,26 Several authors reported the routine use of CSF diversion procedures, including lumbar drainage or lumbar fenestration, 27,28 when intraoperative CSF leaks occur. However, due to the very low incidence rates of postoperative CSF leaks in the present study and other previously reported studies, 9,13 as well as the potential to aggravate an ascending infection caused by lumbar drainage if postoperative CSF rhinorrhea is present, routine use of any CSF diversion technique was not performed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although, this is a common site for many neurosurgeons and no incision siterelated complications occurred in the present study, some authors suggest a periumbilical incision for better cosmetic results (►Table 2). 13,26 Several authors reported the routine use of CSF diversion procedures, including lumbar drainage or lumbar fenestration, 27,28 when intraoperative CSF leaks occur. However, due to the very low incidence rates of postoperative CSF leaks in the present study and other previously reported studies, 9,13 as well as the potential to aggravate an ascending infection caused by lumbar drainage if postoperative CSF rhinorrhea is present, routine use of any CSF diversion technique was not performed.…”
Section: Discussionmentioning
confidence: 99%
“…9,10 Numerous techniques including autologous grafts or artificial materials have been described for sellar reconstruction to prevent postoperative CSF leaks. [9][10][11][12][13][14] Among the techniques, using fat and/or fascia grafts harvested from the patient's abdomen or thigh has been suggested in many studies as an important effective method to control CSF leaks, resulting in avoidance of lumbar drain, and long-term bedrest with decreased hospital stays. 9,13,15 In the present study, we report a single surgeon's experience with EETSA for pituitary adenomas and the clinical results of sellar floor reconstruction using autologous abdominal fat grafts for intraoperative CSF leaks.…”
Section: Introductionmentioning
confidence: 99%
“…11,12 In the case of an intraoperative CSF leak however, it appears to be generally accepted throughout the literature that sellar floor reconstruction should take place to prevent postoperative meningitis. 13 Other techniques to try and prevent recurrence such as instillation of alcohol into the pituitary fossa have failed to show an improvement in recurrence rates, and will not be addressed in this study. 5…”
Section: Introductionmentioning
confidence: 97%
“…The frequency of postoperative CSF leaks depends on many factors as the technique used for reconstruction of the sellar floor and the skull base bony defect, and has been observed in as many as 5 to 75% of cases (Gardner et al, 2008a,b;Stippler et al, 2009;Greenfield et al, 2010). CSF leaks can lead to complications such as infection and pneumoencephalus, which may lead to further comorbidities, longer recovery times and increased hospital costs (Conger et al, 2018;Roca et al, 2018).…”
mentioning
confidence: 99%
“…Different techniques and materials have been reported in the literature for reconstruction of these skull base defects including the use of fat grafts, autologous muscle, fascia lata, vascularized mucosal flaps, non-vascularized autografts, and different synthetic materials (Conger et al, 2018;Roca et al, 2018). They include bio-absorbable implants as collagen sponges (Kelly et al, 2001), dura mater substitute (Sandoval-Sánchez et al, 2012;Al-Asousi et al, 2017), fibrin glue, Polyethylene glycol (PEG) hydrogel dural sealant (Cosgrove et al, 2007;Burkett et al, 2011), polydioxanone plates and non-absorbable implants as porous polyethylene plates and titanium mesh (Al-Asousi et al, 2017).…”
mentioning
confidence: 99%